Insights into the role of hepatocyte PPARα activity in response to fasting - Régnier, Marion (2020)
The liver plays a central role in the regulation of fatty acid metabolism. Hepatocytes are highly sensitive to nutrients and hormones that drive extensive transcriptional responses. Nuclear hormone receptors are key transcription factors involved in this process. Among these factors, PPARα is a critical regulator of hepatic lipid catabolism during fasting. This study aimed to analyse the wide array of hepatic PPARα-dependent transcriptional responses during fasting. We compared gene expression in male mice with a hepatocyte specific deletion of PPARα and their wild-type littermates in the fed (ad libitum) and 24-h fasted states. Liver samples were acquired, and transcriptome and lipidome analyses were performed. Our data extended and confirmed the critical role of hepatocyte PPARα as a central for regulator of gene expression during starvation. Interestingly, we identified novel PPARα-sensitive genes, including Cxcl-10, Rab30, and Krt23. We also found that liver phospholipid remodelling was a novel fasting-sensitive pathway regulated by PPARα. These results may contribute to investigations on transcriptional control in hepatic physiology and underscore the clinical relevance of drugs that target PPARα in liver pathologies, such as non-alcoholic fatty liver disease.